2015
DOI: 10.1534/genetics.115.179465
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Meiotic Recombination by CENP-B Homologs inSchizosaccharomyces pombe

Abstract: Meiotic homologous recombination (HR) is not uniform across eukaryotic genomes, creating regions of HR hot- and coldspots. Previous study reveals that the Spo11 homolog Rec12 responsible for initiation of meiotic double-strand breaks in the fission yeast Schizosaccharomyces pombe is not targeted to Tf2 retrotransposons. However, whether Tf2s are HR coldspots is not known. Here, we show that the rates of HR across Tf2s are similar to a genome average but substantially increase in mutants deficient for the CENP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 65 publications
1
5
0
Order By: Relevance
“…According to the organization of this construct, only cells in which splicing of the artificial intron was completed in the Tf2-12 mRNA will allow G418 resistance after a new Tf2-12 cDNA mobilization. The absence of Abp1 clearly increased the transposition frequency of Tf2-12 ( Figure 3B), consistent with recent results analyzing Tf2 transposition frequency (Johansen and Cam 2015;Murton et al 2016). In contrast, the twofold increase in Tf2 mRNA level detected in pab2D cells did not result in a noticeable increase in the rate of Tf2 transposition ( Figure 3B).…”
Section: The Increased Frequency Of Tf2 Transposition In Abp1d Cells supporting
confidence: 91%
See 1 more Smart Citation
“…According to the organization of this construct, only cells in which splicing of the artificial intron was completed in the Tf2-12 mRNA will allow G418 resistance after a new Tf2-12 cDNA mobilization. The absence of Abp1 clearly increased the transposition frequency of Tf2-12 ( Figure 3B), consistent with recent results analyzing Tf2 transposition frequency (Johansen and Cam 2015;Murton et al 2016). In contrast, the twofold increase in Tf2 mRNA level detected in pab2D cells did not result in a noticeable increase in the rate of Tf2 transposition ( Figure 3B).…”
Section: The Increased Frequency Of Tf2 Transposition In Abp1d Cells supporting
confidence: 91%
“…Specifically, it was shown that the CENP-B homolog, Abp1/Cbp1, promotes histone deacetylation and heterochromatin formation at Tf2 loci by recruiting the histone deacetylases Clr3 and Clr6 (Cam et al 2008). Binding of Abp1 to LTRs also promotes the clustering of Tf2 elements into specialized higher-order structures (Cam et al 2008), which appear to restrict homologous recombination between cDNAs and preexisting Tf2 (Johansen and Cam 2015;Murton et al 2016).…”
mentioning
confidence: 99%
“…Heterochromatin spreading is partly limited by tRNA genes, which are known to contribute to fork pausing [ 101 , 102 , 103 , 104 ]. The intriguing overlap of the fork termination protein Sap1 and Cenp-B homologues in the limiting rearrangement of LTR repeats elsewhere in the genome (e.g., [ 113 , 114 ]) and suggests that one function for the Cenp-B homologues at the centromere may be limiting rearrangements.…”
Section: Discussionmentioning
confidence: 99%
“…Cenp-B homologues have been linked to origin binding and to centromere maintenance [ 107 , 108 , 110 , 111 , 112 ]. Importantly, they are also involved in resisting rearrangements at long terminal repeats (LTRs) that are associated with transposons throughout the genome [ 113 , 114 ]. The Cenp-B proteins act antagonistically with a sequence-specific binding protein associated with fork arrest, Sap1 [ 113 , 115 , 116 ].…”
Section: Centromere Dynamicsmentioning
confidence: 99%
“…Like cohesin, condensin is found enriched at axial cores of meiotic chromosomes by cytology (Viera et al, 2007, Yu andKoshland, 2003) and plays an important role in the formation of the synaptonemal complex (SC), a ladder-like nucleoprotein assembly that connects homologous chromosome pairs in the process of recombination (Hernandez et al, 2018, Yu andKoshland, 2003). In addition, condensin regulates DSB formation in C. elegans (Hernandez et al, 2018, Mets andMeyer, 2009) and suppresses illicit recombination of repetitive DNA in S. cerevisiae and S. pombe (Li et al, 2014, Johansen andCam, 2015).…”
Section: Introductionmentioning
confidence: 99%